Educação em ciências e seu compromisso com a saúde: aterosclerose como ferramenta pedagógica - Pasquali, Ísis Samara Ruschel (2013)
The world population is living longer, but are sicker, says a survey performed by the Global Burden of Disease Study, in 2010. The chronic diseases (CD) as hypertension, obesity, diabetes, cardiovascular diseases (CVD), among others, are the leading causes of death worldwide. In Brazil, according to the Ministry of Health, 72% of deaths are due to chronic diseases, particularly to atherosclerosis, a cardiovascular disease, that may start in childhood. These diseases have in common the maintenance of unhealthy lifestyle habits, as the main responsible for the incidence of cases. Adequate knowledge is a major factor in combating unhealthy lifestyles, and the school is the appropriate environment to develop such knowledge. This study examined the applicability of cross-cutting theme health (CTS) in public elementary schools in Santa Maria / RS, in order to remedy problems identified by teachers, when seeking to develop this theme in order to assist in the development of health education in school. The search is structured in two stages. The first involved the participation of 104 teachers and to sought to check if they develop the CTS in their classes. If believe themselves to be able to solve this task, they received some form of training to accomplish this task and what problems they face in fulfilling the requirements of the MEC regarding the development of CTS. The results show that teachers, in general, seek to develop health issues in their classes, but do not feel prepared for this task. The most noted was the lack of teaching materials to support teaching about health. Thus, the project involved the creation of two notebooks of activities, one for the lower grades (1st to 5th grade), and one for the upper grades (6th to 9th grade) of the elementary school about atherosclerosis, due to high incidence of cases in Brazil, and approach of multiple health problems related to quality of life of school, which can be exploited from this theme. The activities were created or adapted for the UFSM and FURG medicine undergraduates, as recommended by the author of this thesis. After making the notebooks the researcher applied the second phase of research that aimed to collect data on the evaluation of teachers about the material created. This step was made by a workshop provided an opportunity to raise awareness about the importance of CVD´s prevention, particularly atherosclerosis since childhood. During the workshop the teachers manipulated, read, suggested changes and evaluated the material and subject atherosclerosis through a pre- and post-test, showing 88,65% acceptance in relation to its use, and its validation as an important tool to aid in the implementation of the thematic school. The research used semi-structured questionnaires and participant observation as tools for data collection, based on social research methods Gil (2011). For data interpretation, with qualitative and quantitative evaluation, we used content analysis, based on the theory of Bardin (2011) and Yin (2001). With support from the City Department of Education, and the City Council of Santa Maria, the material will be distributed to local schools, with the promise of incentive campaigns school on cardiovascular health since childhood.